Determinants of organic turmeric (Curcuma longa) cultivation in hill states of India: A logit approach - RAM SINGH; SHIV KUMAR; SUKHEIMON PASSAH; S M FEROZE (The Indian Journal of Agricultural Sciences, 2022)
The study demonstrates the economic and social determinants in adoption of organic cultivation of turmeric (Curcuma longa L.) in the states of Mizoram, Meghalaya, Manipur and Sikkim. The turmeric production through organic method demonstrated high yield and returns. The yield and returns of turmeric crop were found significantly higher in the adopter state than non-adopter states of the region. The analysis of economic returns showed organic cultivation of turmeric to be economically feasible but it also suggested policy implications like post-harvest arrangements. The factor share analysis stressed on need of pre-harvest arrangements on the turmeric farm of adopter as well as non-adopter states to make the crop more remunerative across the states of NEHR. The ANOVA analysis of yield contrasts provided the way forward to the capability and ability of turmeric yield across the states in the region. The identified technical as well as social factors and determinants through logit analysis have provided the researchable issues to enhance the productivity and production of organic turmeric in the region.